A rare complication of acute lower limb ischemia post coronavirus disease 2019 infection in a healthy pediatric patient: case report - Arwa Badr; Khayria AlSofyani; Yara AlGoraini (BMC Pediatrics, 2023)
Abstract Background Coronavirus Disease 2019 (COVID-19) is a novel respiratory disease that first emerged in 2019. Patients infected with this disease present with a myriad of symptoms. Limb ischemia and hypercoagulability are complications identified in adults. COVID-19-related vasculitis is a known but seldom reported complication in pediatric patients, and the treatment approach is still not well established. Case presentation We report the case of a healthy four-year-old female with a history of COVID-19 who developed acute lower limb ischemia. This was initially treated as a case of acute snake envenomation by administering snake antivenom with no improvement. She eventually developed lower limb acrocyanosis with an inability to ambulate. The patient was started on interleukin-6 receptor inhibitors (tocilizumab), anticoagulants, and pulse steroid therapy. The patient had complete resolution with the loss of only one toe. Conclusion Identification of thromboembolic complications in pediatric patients with no comorbidities and a history of COVID-19 can be difficult. Early recognition and treatment have a major impact on morbidity and can increase the likelihood of limb salvage.